REPRESENTASI SUSTAINABILITY PADA KEMASAN KOSMETIK DALAM RANGKA KOMODIFIKASI : SUSTAINABLE MYTH REPRESENTATION ON INNISFREE COSMETIC PACKAGING IN THE FRAMEWORK OF COMMODIFICATION - Dipa Sandi Dewanty; Agung Eko Budiwaspada; Cama Juli Rianingrum (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2024)
High competition between brands encourages marketers to be more creative in maximizing marketing strategies, one of which is through product packaging design. Some cosmetic manufacturers that use a commodification strategy in packaging design are Innisfree, which uses the concept of sustainable packaging. The emergence of commodification practices in packaging design visualization is studied through the sign system that appears on the packaging to understand the meaning contained therein and understand these signs through the meaning of connotations and myths. How does the sustainable concept, the display of verbal and visual elements in packaging design such as color, logo, typography, and images/illustrations become a product commodification strategy by transforming use value into exchange value through sustainable meanings. The aim of the research is to understand sustainable materials used in packaging structures, and understand sustainable representation through packaging design elements used in packaging as a form of commodification. This research is a type of descriptive qualitative research with a case study method. Data collection was carried out using non-participant observation techniques, documentation and literature study. Data analysis uses SPC's Sustainable Packaging criteria to identify sustainable packaging standards used by cosmetic products. Roland Bathes' theory was used to obtain ideologies and myths, then researchers used commodification theory as an effort to answer the formulation of signs used as a commodification strategy. The results of this research indicate the practice of visual commodification, where commodification is formed from material and narrative differences in the visual elements used. So it can be concluded that the concept of sustainable packaging design can be constructed if the materials and visual elements can represent sustainable products holistically.